Enhanced differentiation of the mouse oli-neu oligodendroglial cell line using optimized culture conditions - Guillermo Rodriguez Bey; Quasar Saleem Padiath (BMC Research Notes, 2023)
Abstract Objective Oligodendrocytes (OL) are the glial cell type in the CNS that are responsible for myelin formation. The ability to culture OLs in vitro has provided critical insights into the mechanisms underlying their function. However, primary OL cultures are tedious to obtain, difficult to propagate and are not easily conducive to genetic manipulation. To overcome these obstacles, researchers have generated immortalized OL like cell lines derived from various species. One such cell line is the mouse Oli-neu line which is thought to recapitulate characteristics of OLs in early stages of maturity. They have been extensively utilized in multiple studies as surrogates for OLs, especially in analyzing epigenetic modifications and regulatory pathways in the OL lineage. Results In this report we present the development of optimized culture media and growth conditions that greatly facilitate the differentiation of Oli-neu cells. Oli-neu cells differentiated using these new protocols exhibit a higher expression of myelin related genes and increased branching, both of which are defining characteristics of mature OLs, when compared to previous culture protocols. We envision that these new culture conditions will greatly facilitate the use of Oli-neu cells and enhance their ability to recapitulate the salient features of primary OLs.